Use of Scenario Method for Environmental States In the City Marketing Under the Covid-19 Pandemic - Anna CZAPLIŃSKA (Communications of International Proceedings, 2021)
As a result of the progressive Covid-19 Pandemic, rapidly changing socio-economic relationships are particularly evident on a national and sometimes even regional scale, as a number of countries have chosen their own package of rescue solutions for their societies and economies, which are revised on an ongoing basis.  Thus, the environment became labile. Considering the fact that under pandemic threat, the vast majority of the so-called strengths of a place are no longer relevant, marketing activities face serious difficulties. The purpose of this study was to identify the determinants of local (urban) marketing activity in a strategic perspective in light of the dynamic changes occurring in its environment under the Covid-19 Pandemic. A scenario method for the environment states was applied in order to identify better those components of the macro-environment that may have a decisive impact on the image and brand of the city and future marketing activities. According to the results obtained, it seems that the anticipated changes in the technological sphere can influence the planned marketing activities most positively.  On the other hand, in the socio-cultural sphere, there is no positive process that would affect the marketing activities of cities. Furthermore, most of the processes included with negative impact have high and medium impact, which emphasizes their importance further.  It is important and, at the same time, dangerous because socio-cultural processes usually take place in the long term, and their change is sometimes impossible to implement, regardless of the resources involved. Apart from the socio-cultural sphere, most negative factors occur in the economic sphere. Some of them have a maximum negative influence. In this case, however, regulations could occur much faster, provided that we are aware of the processes in progress, their interrelationships and simple goodwill, which is sometimes difficult to find.
Keywords: City Marketing; Covid-19 Pandemic; Scenario Method for Environment States